Penerapan Model Pembelajaran Numbered Heads Together (Nht) Untuk Meningkatkan Hasil Belajar Siswa Tentang Keberagaman Karakteristik Individu Pada Mata Pelajaran PPKN Kelas IV SD Negeri Glonggong - Santi Khasiatin Nisa; Nur Fajerie; Sri Surachmi (Peneliti.net, 2023)
The low learning outcomes of PPKn indicate that learning goals have not been achieved. It can be seen from the results of the daily test scores of grade IV students of SD Negeri Glonggong that diversity material as a gift of God shows that 7 out of 27 students or 26% of students are complete and 20 students or 74% are not complete. The reason is that students dare not ask questions, students have not dared to come forward to do assignments, and many students find KDP lessons boring. The purpose of the study is to improve the learning outcomes of PPKn material diversity of individual characteristics. The research stage includes planning, observation and reflection. From the results of the action, it shows an increase in ppkn learning outcomes material diversity of individual characteristics, it can be seen from the results of student learning evaluation in the pre-cycle reaching 26%, increasing in cycle I 70%, cycle II 100% so that there is an increase from pre-cycle to cycle II by 74%. The Numbered Heads Together (NHT) learning model can improve learning achievement, make the learning process fun, increase student activity in the PPKn learning process, material diversity of individual characteristics in grade IV subjects at SD Negeri Glonggong.